The effect of private health insurance on self-assessed health status and health satisfaction in Germany - René Petilliot (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
In Germany, private health insurance covers more innovative and costly treatments than public insurance. Moreover, privately insured individuals are treated preferentially by doctors. In this article, I use subjective health data to examine whether these superior features of private insurance actually transfer into better health. I focus on German adolescents who are still in education to control for selection and account for differences in health-conscious behavior between publicly and privately insured individuals. I find that privately and publicly insured individuals do not differ in health, which contrasts with previous research. Hence, doctors appear to be the sole profiteers of the private insurance system and billions of euros could be saved by aligning private and public health insurance.
Keywords: I11; I12; I13; I18; I31; 330; Health satisfaction; Self-assessed health status; Private health insurance; Public health insurance; Selection